PENERAPAN EDUTAINMENT DALAM MENINGKATKAN KEMAMPUAN EKSPLORATIF ANAK USIA DINI - Eka Setiawati; Suci Aprilyati R; Ayu Fajarwati; Yusdiana Yusdiana (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
The type of research used was a class action on the subject of a kober and nisa group's 14 children. This type of study is the classroom action study that is focused on a classroom or classroom action called the risearch classroom. The data gathering tool consists of observation, interviews, and documentation. The data analysis of class action research is carried out in a series of steps with multiple cycles, in a cycle of four stages of planning, execution of actions, observation, and reflection. The precautionary activities that led to the study produced data that the average value of new people's exploration capabilities reached 27.41%. Action in research of this ability to explore is carried out in two cycles. Based on cycle ii, the average child's ability has reached an 85.28%. These developments have reached success indicators where research is said to be successful when it reaches 76%. Thus, the study may be said to be successful.